(untitled) (Iraqi Journal of Market Research and Consumer Protection, 2023)
In order to evaluate the performance of double-cross maize hybrids in planting dates suitable for fall growing season in the middle region of Iraq, a field experiment was conducted at the fields of the College of Agricultural Engineering Sciences - University of Baghdad - Jadriya for the fall season of 2022 using double-cross maize hybrids selected from fifteen double cross hybrid maize resulted from crossing ten single hybrids resulting from crossing five inbred lines using the half-diallel method. These included Hybrid 1 = (1×4)(3×5) from the crossing of (ZM49W3E x CDCNS) (ZM43WIZE x ZM19), Hybrid 2 = (1×2)(3×5) from the crossing of (ZM49W3E × CDCN5) (ZM43WIZE x ZM60), Hybrid 3 = (1×5)(2×4) from the crossing of (ZM60 × ZM19) (ZM43WIZE ×CDN5), Hybrid 4 = (1×2)(4×5) from the crossing of (ZM19 × CDCN5) (ZM43WIZE ×ZM60), and Hybrid 5 = (1×4)(2×3) from the crossing of (ZM60 × ZM49W3E) (ZM43WIZE × ZM19), and their comparison with the synthetic variety IPA5018, and testing them under three planting dates: July 1st, July 15th, and August 1st. The experiment used a randomized complete block design with four replications arranged in a split-plot design. The main plots included the three planting dates, while the subplots included the five double-cross maize hybrids and the control variety. Yield and yield components were studied. The results of the experiment showed high significant effects for the third planting date for all traits except for the number of ears per plant, where the third planting date was superior in the number of grains per ears 660.4, weight of 100 grains 37.83 g , days to physiological maturity 99.67 days, crop growth rate 5.644 g plant-1 day-1, and yield per unit area 14.95 ton ha-1. The superiority of the hybrid (1×2)(3×5) in the number of grains ear-1 and the weight of 100 grains was 542.3 and 36.37, respectively., and this was reflected on the yield per unit area, which reached 11.69 ton ha-1, while hybrid (1×2) (3×5) outperformed in number of ears per plant 1.400 and the same hybrid was the earliest to reach physiological maturity at 97.50 days. The response of the double-cross maize hybrids varied with different planting dates and gave significant interaction for all studied traits except for the number of ears per plant.